2022
DOI: 10.3390/ijerph19041967
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Mixed Education Mode for the Safety Engineering Major during the Coronavirus (COVID-19) Epidemic

Abstract: During the COVID-19 epidemic, many countries faced a critical situation in terms of the global economy and human social activities, including education. In China, the coronavirus is better controlled. Chinese university students have returned to school to study. Despite previous research on online education and learning, the readiness of students for the online and offline learning models implemented at this particular time is not well understood. This paper discusses a hybrid education model for undergraduate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 49 publications
(47 reference statements)
3
7
0
Order By: Relevance
“…Although the non-availability of year 2018 data on students' performance in Advanced Thermofluids as shown in Figure 8 may affect the confidence level in making overall judgment on the potential influence of online learning mode as compared to offline, the descriptive analysis of results illustrated in Figure 8 notwithstanding shows the betterment of virtual learning mode as against in-person approach. The foregoing results are comparable with the results obtained from many authors such as [9,20,23] on the beneficial influence of virtual mode of instructions. Again, it can be seen in Figure 9 that there was no available data for students' performance in Advanced Thermofluids in the year 2018.…”
Section: Rq3: Does Mode Of Instruction Significantly Influence Academ...supporting
confidence: 89%
See 4 more Smart Citations
“…Although the non-availability of year 2018 data on students' performance in Advanced Thermofluids as shown in Figure 8 may affect the confidence level in making overall judgment on the potential influence of online learning mode as compared to offline, the descriptive analysis of results illustrated in Figure 8 notwithstanding shows the betterment of virtual learning mode as against in-person approach. The foregoing results are comparable with the results obtained from many authors such as [9,20,23] on the beneficial influence of virtual mode of instructions. Again, it can be seen in Figure 9 that there was no available data for students' performance in Advanced Thermofluids in the year 2018.…”
Section: Rq3: Does Mode Of Instruction Significantly Influence Academ...supporting
confidence: 89%
“…Generally, descriptive analysis has shown that the online learning mode yielded better academic performance for students when compared to the in-person mode in respect of all the four mechanical engineering courses considered in this study. The beneficial influence of the online learning mode, deduced based on the results obtained from the preliminary descriptive analysis carried out, was similarly reflected in the findings of many authors [8,9,[20][21][22][23]. Relying on the preliminary outcomes acquired from the descriptive analysis used in this study, the perceived positive impacts of the online learning mode can be attributed to some of its associated advantages.…”
Section: -Discussionsupporting
confidence: 79%
See 3 more Smart Citations